2020
DOI: 10.1038/s41380-020-0711-y
|View full text |Cite
|
Sign up to set email alerts
|

GABA-A receptor differences in schizophrenia: a positron emission tomography study using [11C]Ro154513

Abstract: A loss of GABA signaling is a prevailing hypothesis for the pathogenesis of schizophrenia. Preclinical studies indicate that blockade of the α5 subtype of the GABA receptor (α5-GABA A Rs) leads to behavioral phenotypes associated with schizophrenia, and postmortem evidence indicates lower hippocampal α5-GABA A Rs protein and mRNA levels in schizophrenia. However, it is unclear if α5-GABA A Rs are altered in vivo or related to symptoms. We investigated α5-GABA A Rs availability in antipsychotic-free schizophren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
52
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 70 publications
2
52
1
Order By: Relevance
“…Of note, these data were collected in naïve animals, lacking any features relevant to the pathophysiology of schizophrenia. In this context, a recent PET study reported reduced [ 11 C]-Ro15–4513 V T in the hippocampus of antipsychotic-naïve schizophrenia patients, whilst no group differences were found in a second cohort of patients who were taking antipsychotics ( Marques et al., 2020 ). One interpretation of these data is that antipsychotics may have a “normalizing” effect and it is tempting to speculate that this is consistent with the increases seen in GABA A R availability herein.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Of note, these data were collected in naïve animals, lacking any features relevant to the pathophysiology of schizophrenia. In this context, a recent PET study reported reduced [ 11 C]-Ro15–4513 V T in the hippocampus of antipsychotic-naïve schizophrenia patients, whilst no group differences were found in a second cohort of patients who were taking antipsychotics ( Marques et al., 2020 ). One interpretation of these data is that antipsychotics may have a “normalizing” effect and it is tempting to speculate that this is consistent with the increases seen in GABA A R availability herein.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, to date, no studies have examined the potential impact of antipsychotic drug exposure using radioligands with greater selectivity for GABA A -BZR containing α1/α5 subunits, such as Ro15-4513 ( Lingford-hughes et al., 2002 ; Maeda et al., 2003 ). This is of clinical relevance, as a recent PET study in schizophrenia found reduced volume of distribution (V T ) of [ 11 C]- Ro15–4513 relative to healthy controls only in antipsychotic-naïve schizophrenia patients, whilst no group differences were found in antipsychotic-medicated schizophrenia patients relative to healthy controls ( Marques et al., 2020 ). Furthermore, convergent lines of evidence from animal models strongly suggest that allosteric modulators of α5GABA A R have potential as novel, non-dopaminergic antipsychotic compounds, by balancing hippocampal excitation via tonic inhibition of pyramidal neurons ( Bonin et al., 2007 ; Caraiscos et al., 2004 ; Donegan et al., 2019 ; Gerdjikov et al., 2008 ; Gill et al., 2011 ; Hauser et al., 2005 ; Semyanov et al., 2004 ; Towers et al., 2004 ).…”
Section: Introductionmentioning
confidence: 85%
“…The α5-containing GABA-A receptor represents less than 5 percent of all GABA-A receptors and has a restricted distribution within the prefrontal cortex, hippocampus, and amygdala (Gill and Grace, 2014). Abnormalities in the GABA-A receptor have been observed extensively in SCZ (Marques et al, 2020; Rudolph and Möhler, 2014) and allosteric modulation of the α5-containing GABA-A receptor has been proposed to have the potential to ameliorate cognitive deficits in SCZ (Gill and Grace, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, to date, no studies have examined the potential impact of antipsychotic drug exposure using radioligands with greater selectivity for GABA A -BZR containing α1/α5 subunits, such as Ro15-4513 (Lingford-hughes et al, 2002;Maeda et al, 2003). This is of clinical relevance, as a recent PET study in schizophrenia found reduced volume of distribution (V T ) of [ 11 C]-Ro15-4513 relative to healthy controls only in antipsychotic-naïve schizophrenia patients, whilst no group differences were found in antipsychotic-medicated schizophrenia patients relative to healthy controls (Marques et al, 2020). Furthermore, convergent lines of evidence from animal models strongly suggest that allosteric modulators of α5GABA A R have potential as novel, non-dopaminergic antipsychotic compounds, by balancing hippocampal excitation via tonic inhibition of pyramidal neurons (Bonin et al, 2007;Caraiscos et al, 2004;Donegan et al, 2019;Gerdjikov et al, 2008;Gill et al, 2011;Hauser et al, 2005;Semyanov et al, 2004;Towers et al, 2004).…”
mentioning
confidence: 99%